Isomerização do n-Hexano por platina suportada na zeólita H-ZSM-5 : efeito do teor de alumínio - Gomes, Fagner Alves (2011)
The objective of this study was to verify the influence of the Si/Al ratio (11.5, 15.0, 25.0, 40.0 and 140.0) in zeolite ZSM-5 in the conversion, activity, selectivity and stability as bifunctional catalysts (Pt/H-ZSM-5) applied to the isomerization reaction of n-hexane. To prepare the bifunctional catalysts, initially the zeolites were submitted, successively, to ion exchange with ammonium cations, ion exchange cations with platinum, calcination and activation process. From the results of the isomerization of n-hexane, it was observed that with the increase of the Si/Al ratio, that is, decreasing the amount of aluminum, there was a reduction in activity and conversion. This is due to decrease the number of acid sites present, responsible to isomerize the carbocation generated in these sites. In contrast, the increase of the Si/Al ratio leads to a better selectivity to the formation of isomers. Among the catalysts, the Pt/H-ZSM-5 (15.0) showed the best result of conversion and activity. In order to compare the Pt/H-ZSM-5 catalysts, the reaction was carried out using the isomerization catalyst Pt/H-Beta (9.0). This catalyst had the best result that all the others, this result may possibly be due to increased acidity of the material and its morphological characteristics, such as type and diameter of pores etc. and/or the crystallite size of zeolites used.